PENGARUH TERAPI QUR’AN TERHADAP PERUBAHAN INTENSITAS NYERI PADA PASIEN RAWAT INAP DI RUMAH SAKIT UMUM DAERAH KALISAT JEMBER - Trisna Vitaliati (Jurnal Kesehatan dr. Soebandi, 2013)
The effects of the disease on the body will cause pain. Pain experienced by hospitalized patients have pain intensity vary. Pain is the most common reason people seek medical care. Pain can be a major factor that hinders the ability and willingness of individuals to recover from an illness. Pain management with non-pharmacological means should be applied. But the ground reality of clients who complained of pain immediately given analgesics and ignore the non farmakolagi Qur'an as therapy. Yet what is important to note that in addition to drug delivery is mentally and emotionally clients. This study aims to find out is there any "Qur'an therapeutic effect to changes in pain intensity in hospitalized patients." This research is to design pre ekspeimental experiment (pre-experimental design) by using a one group pre-test and post-test took place in hospitals Kalisat Jember. The sampling method with a total sampling with 61 respondents. Test analysis in this study is the Wilcoxon matched pairs test and Friedman with SPSS version 12 mengngunakan. Research suggests that there are differences obtained pain scale before therapy after Qur'an therapy. Treatment Qur'an therapy in hospitalized patients between 1st day, 2nd day and 3rd day had a significant influence in the amount based on the value of significance 0.000 where sig <0.05.